Study of Mechanical and Tribological Properties of Bulk MgO-MgFe2O4 Ceramic Nanocomposites Developed Via Solid State Precipitation - Kumar Singh, Mahesh (My University, 2014)
Bulk polycrystalline ceramics, such as MgO, are refractory and stiff materials, which may be suitable for various advanced structural applications, especially involving elevated temperatures. However, this requires considerable improvement in the mechanical and tribological properties, which are deemed possible in the presence of second phase particles in the nanosized regime. Moreover, the processing of such ceramic nanocomposites via the usual powder metallurgical route is not feasible for large scale commercial productions. Against this backdrop, the ongoing research at IIT Bombay is focused on developing commercially friendly processing routes, based on solid-state precipitation of nanosized second phase particles during controlled aging treatments of dense supersaturated solid solutions based on MgO. The reported work concentrates on evaluation and understanding of some of the important mechanical (via Vickers indentation, compression and 3-Point bending tests) and tribological properties (via abrasive wear tests) of MgO-MgFe2O4 ‘nanocomposites’, developed via the aforementioned route. Effect of aging durations at 1000oC of the dense supersaturated solid solutions of Fe3+ in MgO (post sintering-cum-solution treatment) on the mechanical and tribological properties were investigated in detail. The aging treatment led to the formation of nanosized MgFe2O4 precipitate particles at grain boundaries as well as homogeneously within the grains. In general, it was observed that increase in aging duration lead to improvement of the hardness, fracture toughness and fracture strengths. Hardness increased by more than 50% upon aging for optimized duration. Similar trend for the variation of the abrasive wear resistance with aging duration was also observed. Such considerable increase in mechanical and tribological properties of MgO-based nanocomposites, produced via a commercially friendly route, is believed to lead to a breakthrough in the usage of this otherwise promising refractory ceramics for advanced structural applications.
MT, SPMS
Keywords: Magnesioferrite; Spinel